A new strategy for the determination of trace Hg2+ by 5CB liquid crystal RRS probe based on nanogold amplification and Galvanic replacement reaction. Issue 4 (16th March 2022) - Liang, Aihui; Shu, Yiyi; Huang, Xiaofang; Li, Dan; Zhi, Shengfu; Li, Chongning; Jiang, Zhiliang
ABSTRACT: In pH 3.1 HCOOH-HCOONa buffer solution, liquid crystal 5CB was used as the probe to generate a strong resonance Rayleigh scattering (RRS) peak at 450 nm. Gold nanoparticles (AuNPs) could catalyse the reaction of phosphomolybdic acid (PMo)-formic acid (FA) to form phosphomolybdenum blue (PMoB), which caused the RRS strength of PMo at 450 nm to decrease linearly. Hg 2+ could have an electrostatic substitution reaction with AuNPs, thereby inhibiting the catalytic effect of AuNPs, and the RRS peak was enhanced. In the range of 2.5 × 10 −9 mol/L–4.5 × 10 −8 mol/L Hg 2+, as the concentration of Hg 2+ increased, the catalytic effect of AuNPs gradually weakened, and the peak value of RRS at 450 nm (ΔI) was linearly increased. The regression equation is ΔI450nm = 27.988C−5.6159, and the detection limit is 1.0 nmol/L. The method has been used to detect Hg 2+ in wastewater with satisfactory results. Graphical abstract: uf0001